2013
DOI: 10.4103/0976-9668.107253
|View full text |Cite
|
Sign up to set email alerts
|

Role of curcumin in systemic and oral health: An overview

Abstract: Various modalities of treatment are available for different dental diseases, but the major drawback of these conventional drug therapies is the numerous side effects associated with their use. This has led to renewed interest in the discovery of novel anti-infective natural compounds derived from plants. Plants have been the major source of medicine since the time immemorial. Turmeric has been attributed a number of medicinal properties in the traditional system of medicine. The objective of this article is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(46 citation statements)
references
References 28 publications
0
45
0
1
Order By: Relevance
“…2F)58. Other general constituents include proteins, resins and sugars59. Some volatile components could be lost by drying the rhizomes at 40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…2F)58. Other general constituents include proteins, resins and sugars59. Some volatile components could be lost by drying the rhizomes at 40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Turmeric is an abundant medicinal herb majorly cultivated in Asia and is widely used in food industries as a colouring agent or food additive [19]. One of its major components, curcumin [20], plays an important role in the treatment of periodontal diseases and oral cancers [21]. Turmeric exhibits numerous therapeutic properties such as antioxidant, anti-inflammatory, anticancer, antiviral and antibacterial activities [22].…”
Section: Introductionmentioning
confidence: 99%
“…2527 Curcumin is known to have antiseptic and anti-inflammatory properties, along with several other therapeutic properties. 28,29,30 Although curcumin has low bioavailability, it has been reported that conjugation of curcumin with metal nanoparticles could increase its bioavailability. 31 Also, based on previously reported spectroscopic measurements at various temperatures, the breaking of intra-molecular H-bonding could increase the solubility of curcumin in water at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%